Efficacy of gutta-percha solvents used in endodontic retreatments - Fábio de Almeida Gomes; Ana Paula Barros Daniel; Rodrigo Arraes Nunes; Anna Lygia Nunes Fernandes; Claudio Maniglia-Ferreira; Humberto Ramah Meneses de Matos; Taffarel Canuto Nepomuceno (Revista Sul-Brasileira de Odontologia, 2014)
The aim of this study was to evaluate the effectiveness of four different solvents and classify them according to their potential of action. Material and methods: Four solvents were tested: xylene, eucalyptol, orange oil and chloroform. Twelve gutta-percha points (medium-large), sectioned at 10 mm were used and divided into four groups, resulting in three samples for each solvent. The gutta-percha points were weighed on an analytical balance before being subjected to the action of solvents and subsequently put onto watch glasses that were immersed into the solutions for the following times: 1, 2, 3, 4 and 5 minutes. The percentage of mass loss was registered through weighing after every minute of action of the solvent on the points. Results: All solvents showed the first minute of action as the period of greatest power of dissolution because they act only on the gutta-percha itself and not on the other components of the point, suggesting that at the remaining minutes there would be a lower percentage of dissolution because there was a smaller amount of gutta-percha within the points. Conclusion: Chloroform and xylene showed similar results regarding the rate of dissolution of gutta-percha, yet they were statistically significant higher than eucalyptol and orange oil from 1 to 5 minutes.